"A Little More Ghetto, a Little Less Cultured": Are There Racial Stereotypes about Interracial Daters in the United States?. Issue 2 (April 2020) - Flores, René D.
Negative stereotypes about racial minorities, particularly African Americans, persist in the United States. Given the imperviousness of racial stereotypes about minorities, can individuals who date interracially also be stereotyped? The author investigates this by conducting the first systematic study of men's attitudes toward white and black women who date outside their race. First, the author inductively uncovers these stereotypes through focus groups. Second, to assess these stereotypes' nationwide prevalence and to minimize social desirability bias, the author applies a survey experiment, in which interracial dating is subtly primed via photographs of couples, to a national sample of men. The findings are mixed. In the experiment, crossing the white-black racial boundary does activate negative stereotypes for women, which may have reputational costs, but mostly among older white male respondents. These costs include changes in men's perceptions of their class status, cultural values, and even sexual practices. In conclusion, interracial dating is a key social site where gender-based moral norms are policed, class divisions are constructed, and racial boundaries are maintained.